Predictors of hematoma expansion in intracerebral hemorrhage associated with factor Xa inhibitors - Komatsu, Yoji; Koiso, Takao; Sekine, Tomokazu; Akutagawa, Kazuki; Karita, Hiroki; Kikuchi, Norie; Yamazaki, Tomosato (Frontiers in Neurology, 2025)
BackgroundImproving the outcomes of patients with intracerebral hemorrhage (ICH) associated with factor Xa inhibitors remains a clinical challenge. Andexanet alfa, a specific reversal agent for factor Xa inhibitors, has the potential to mitigate hematoma expansion (HE). The aim of this study is to identify predictors of HE in ICH associated with factor Xa inhibitor use and to propose appropriate indications for reversal therapy.MethodsThis was a single-center, retrospective observational study that included 68 consecutive patients who developed ICH within 24 h of factor Xa inhibitor intake and were not receiving concomitant antiplatelet therapy. The study period spanned from April 2012 to June 2022. The relationships between HE and patient-related, clinical, hematoma-related, and pharmacological factors were examined.ResultsHematoma expansion was observed in 18 cases (26.5%) and significantly worsened outcomes (p = 0.028). In univariate analysis, significant predictors of HE were an irregular margin and/or heterogeneity of the hematoma on computed tomography (CT) (p = 0.009), an initial CT performed within 4 h after drug intake (p = 0.034), and edoxaban use (p = 0.041). A multivariate analysis identified hematoma morphology on CT (p = 0.030) and the initial CT within 4 h after drug intake (p = 0.048) as significant predictors. Hematoma volume, interval from onset to initial CT, and coagulation-related laboratory parameters were not significant.ConclusionThe predictors of HE were an irregular margin or heterogeneous hematoma, and an initial CT performed within 4 h after drug intake. Reversal decisions based on hematoma volume, or interval from onset to initial CT may be inappropriate.